A case report on concurrent occurrence of systemic mastocytosis and myeloid sarcoma presenting with extensive skin involvements and the results of genetic study. Issue 50 (11th December 2020) - Wang, Xinye; Zhang, Lu; Zhou, Daobin; Cai, Hao; Wang, Xuan; Jiang, Xianyong
Abstract: Introduction: Systemic mastocytosis is a rare disease due to mast cell accumulation in various extracutaneous sites. Systemic mastocytosis with an associated clonal hematologic non-MC lineage disease is the second most common subtype of systemic mastocytosis. The most common mutation associated with both systemic mastocytosis and myeloid sarcoma is mutation in Kit . Here, we identified the novel KIT D816V and ARID1A G1254S mutations co-occurring in systemic mastocytosis with myeloid sarcoma. Patient Concerns: A 33-year old male patient presented multiple skin lesions for 10 years. Symptoms accelerated in 2017 with decreased body weight. Physical examination revealed enlarged lymph nodes in his neck, axilla and inguinal region; conjunctival hemorrhage; gingival hyperplasia. Skin biopsy showed mast cell infiltration. Flow cytometry detected CD2, CD25 and CD117 positive cells in lymph nodes. Codon 816 KIT mutation D816V and codon 1245 ARID1A mutation G1254S were found in peripheral blood. MPO, CD117, CD68 positive cells in lymph nodes indicated co-existing myeloid sarcoma. Diagnosis: Systemic mastocytosis with an associated clonal hematologic non-MC lineage disease of myeloid sarcoma Interventions: Cytarabine and daunorubicin for myeloid sarcoma and dasatinib for systemic mastocytosis were initiated. Anti-histamine and anti-leukotrienes therapy were used to prevent NSAIDs-induced shock. Platelets were infused to treat bone marrow suppression. Outcomes: Patient was discharged after recovered from bone marrow suppression. Dasatinib continued on outpatient. Conclusion: This is the first case of patient with systemic mastocytosis and myeloid sarcoma simultaneously presenting extensive skin involvements. Mutations of Kit and Arid1a emphasis the importance to notice possibility of various tumors occurring in patients with multiple mutations. In addition, cysteine-leukotrienes-receptor antagonists should always be used to prevent anaphylactic shock due to mast cell activation.